The language of outsourced call centers a corpus-based study of cross-cultural interaction - Friginal, Eric; EBSCOhost eBook Collection (Amsterdam John Benjamins Pub., 2009)
The Language of Outsourced Call Centers is the first book to explore a large-scale corpus representing the typical kinds of interactions and communicative tasks in outsourced call centers located in the Philippines and serving American customers. The specific goals of this book are to conduct a corpus-based register comparison between outsourced call center interactions, face-to-face American conversations, and spontaneous telephone exchanges; and to study the dynamics of cross-cultural communication between Filipino call center agents and American callers, as well as other demographic groups.
The Language of Outsourced Call Centers -- Editorial page -- Title page -- LCC data -- Table of contents -- List of tables -- List of figures -- Acknowledgements -- Preface -- Chapter 1. Introduction -- Chapter 2. Outsourced call centers in the Philippines -- Chapter 3. Corpora and description of speaker groups in the call center corpus -- Chapter 4. Multi-dimensional analysis -- Chapter 5. Lexico/syntactic features -- Chapter 6. Grammatical expression of stance -- Chapter 7. Politeness and respect markers -- Chapter 8. Inserts -- Chapter 9. Dysfluencies -- Chapter 10. Communication breakdown: caller clarifications.
Electronic reproduction.
Keywords: Intercultural communication -- Philippines; Call center agents -- Philippines -- Language; English language -- Usage; Electronic books